PENGARUH MODEL PEMBELAJARAN BEYOND CENTERS AND CIRCLE TIMES (BCCT) DAN KEMANDIRIAN TERHADAP KREATIVITAS - RUQOYAH, ADIANTI (JPUD - Jurnal Pendidikan Usia Dini, 2016)
This study aims to identify and analyze the influence of the learning model beyond centers and circle times (BCCT) and the child’s independence against group B TK creativity Amanah West Jakarta. A sample of 34 children using Random Sampling technique Stratifeid. The instrument uses a questionnaire of independence and creativity test tool. Testing is done with the correlation validity and reliability testing point biserial Kuder- Richardson reliability coefficients 20. In this study hypothesis test conducted with hotelling t multivariate analysis, independent t test and chi square analysis. The results showed: 1) there are differences in child outcomes that have low creativity among groups and non BCCT bct (T2hitung (36.6)> C2 (11.83)). 2) there are differences in the results of children who have high creativity among groups and non BCCT BCCT (T2hitung (36.6)> C2 (11:45)). 3) There is an interaction effect BCCT learning model and the independence of thecreativity of children (p-value 0.013). 4) There are differences in the results of children who have low self-reliance among groups and non BCCT BCCT (t2hitung (95.51)> c2 (12:33)). 5) there are differences in the results of children who have high self-reliance among groups and non BCCT BCCT (t2hitung (82.47)> c2 (12:33).